∫cosx/[sinx(1+sinx)^2]dx=?求解答过程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:02:29
∫cosx/[sinx(1+sinx)^2]dx=?求解答过程∫cosx/[sinx(1+sinx)^2]dx=?求解答过程∫cosx/[sinx(1+sinx)^2]dx=?求解答过程令t=sinx
∫cosx/[sinx(1+sinx)^2]dx=?求解答过程
∫cosx/[sinx(1+sinx)^2]dx=?求解答过程
∫cosx/[sinx(1+sinx)^2]dx=?求解答过程
令t=sinx cosxdx=dt
原式=∫dt/t(1+t)^2
=∫(1+t-t)/t(1+t)^2dt
=∫[1/t(1+t)-1/(1+t)^2]dt
=∫[1/t-1/(1+t)-1/(1+t)^2]dt
=ln|t|-ln|1+t|+1/(1+t)+C
=ln|sinx/(1+sinx)|+1/(1+sinx)+C
∫(1+sinx)/(1+cosx+sinx)dx
∫[ (sinx * cosx)/(1+(sinx)^4)]/dx
∫cosx/sinx(1+sinx)^2dx
∫cosx/(sinx√sinx)
∫sinx/(sinx-cosx)dx
∫sinx/(cosx-sinx )dx
∫ sinx+cosx/(sinx-cosx)^1/3 dx 求不定积分
求积分:∫ sinx*sinx/(1+cosx*cosx)dx不定积分
∫/(1+sinx+cosx)dx
∫(cosx/1+sinx)dx
∫cosx/(1-sinx)^2
化简:(1+sinx+cosx) / (1+sinx-cosx)
1+sinx-cosx/1+sinx+cosx 化简
化简:sinx/(sinx-cosx) -(sinx+cosx)/(tanx-1)
化简:(sinx)^2/(sinx-cosx)-(sinx+cosx)/((tanx)^2-1)
化简tanx(cosx-sinx)+[sinx(sinx+tanx)]/(1+cosx)
∫cosx / (cosx+sinx)dx
∫dx/(sinx+cosx)